Cellular bases for reward-related dopamine actions. (March 2023) - Yagishita, Sho
Abstract: Dopamine neurons exhibit transient increases and decreases in their firing rate upon reward and punishment for learning. This bidirectional modulation of dopamine dynamics occurs on the order of hundreds of milliseconds, and it is sensitively detected to reinforce the preceding sensorimotor events. These observations indicate that the mechanisms of dopamine detection at the projection sites are of remarkable precision, both in time and concentration. A major target of dopamine projection is the striatum, including the ventral region of the nucleus accumbens, which mainly comprises dopamine D1 and D2 receptor (D1R and D2R)-expressing spiny projection neurons. Although the involvement of D1R and D2R in dopamine-dependent learning has been suggested, the exact cellular bases for detecting transient dopamine signaling remain unclear. This review discusses recent cellular studies on the novel synaptic mechanisms for detecting dopamine transient signals associated with learning. Analyses of behavior based on these mechanisms have further revealed new behavioral aspects that are closely associated with these synaptic mechanisms. Thus, it is gradually possible to mechanistically explain behavioral learning via synaptic and cellular bases in rodents. Highlights: Dopamine activities in the VTA-NAc pathway represent a reward-prediction error to regulate learning. Dendritic spines in D1R- and D2R-SPNs detect transient increases and decreases in dopamine concentration, respectively. Transient dopamine increases effectively enhance plasticity only within a narrow time window. Dissociable sensitivity of D1R- and D2R-dependent synaptic mechanisms regulate generalization and discrimination learning.